Evaluation of Radiant Power of the Light Curing Units Used in Clinics at Governmental and Privates Dental Faculties - Ali Hasan,Sami; Al-Shami,Ibrahim; Al-Hamzi,Mohsen; Alwadai,Ghadeer; Alamoudi,Nada; Alqahtani,Saleh; Daghrery,Arwa; Alaajam,Wafa; Shariff,Mansoor; Kinani,Hussain; Al Moaleem,Mohammed (Medical Devices: Evidence and Research, 2024)
Sami Abdulsalam Ali Hasan,1 Ibrahim Zaid Al-Shami,1 Mohsen Ali Al-Hamzi,1 Ghadeer Saleh Alwadai,2 Nada Ahmad Alamoudi,2 Saleh Ali Alqahtani,2 Arwa Daghrery,3 Wafa H Alaajam,4,5 Mansoor Shariff,6 Hussain Mohammed Kinani,7 Mohammed M Al Moaleem8 1Department of Conservative Dentistry, Faculty of Dentistry, Sanaâ€™a University, Sanaa, Yemen; 2Department: Restorative Dental Science, College of Dentistry, King Khalid University, Abha, Saudi Arabia; 3Department of Restorative Dental Sciences, College of Dentistry, Jazan University, Jazan, 45142, Saudi Arabia; 4Department of Restorative Dental Science, College of Dentistry, King Khalid University, Abha, Saudi Arabia; 5Department of Restorative Dentistry, Faculty of Dentistry, Sanaâ€™a University, Sanaâ€™a, Yemen; 6Prosthetic Department, College of Dentistry, King Khalid University, Abha, 62529, Saudi Arabia; 7Ministry of Health, Sabya General Hospital, Department of Dentistry, Jazan, Saudi Arabia; 8Department of Prosthetic Dental Science, College of Dentistry, Jazan University, Jazan, 45142, Saudi ArabiaCorrespondence: Mohammed M Al Moaleem, Department of Prosthetic Dental Science, College of Dentistry, Jazan University, Jazan, 45142, Saudi Arabia, Email malmoaleem@jazanu.edu.saBackground: Â To evaluate the radiant power of the light cure units (LCUs) in relation to their type, radiant exitance, number of years in clinical use, and condition of LCUs tips in governmental and public clinics in Dental Faculties in Sanaâ€™a City.Materials and Methods: LCUs were collected from different colleges at Sanaa City, Yemen, then LCU data as type, clinical age (< 1 year, between 1â€“ 5 and Ëƒ 5-years), tip condition was visually inspected for damage and adhering debris, and the radiant exitance values of the tested LCUs. Radiant exitance values were subcategorized into three groups: < 400, 400â€“ 850, and > 850 mW/cmÂ², labeled as inadequate, marginal, and adequate radiant exitances, respectively. A Woodpecker radiometer was used with a mode lasting of 20 ...